Pseudomonas aeruginosa ExoU augments neutrophil transepithelial migration. - Michael A Pazos; Bernard B Lanter; Lael M Yonker; Alex D Eaton; Waheed Pirzai; Karsten Gronert; Joseph V Bonventre; Bryan P Hurley (PLoS Pathogens)
Excessive neutrophil infiltration of the lungs is a common contributor to immune-related pathology in many pulmonary disease states. In response to pathogenic infection, airway epithelial cells produce hepoxilin A3 (HXA3), initiating neutrophil transepithelial migration. Migrated neutrophils amplify this recruitment by producing a secondary gradient of leukotriene B4 (LTB4). We sought to determine whether this two-step eicosanoid chemoattractant mechanism could be exploited by the pathogen Pseudomonas aeruginosa. ExoU, a P. aeruginosa cytotoxin, exhibits phospholipase A2 (PLA2) activity in eukaryotic hosts, an enzyme critical for generation of certain eicosanoids. Using in vitro and in vivo models of neutrophil transepithelial migration, we evaluated the impact of ExoU expression on eicosanoid generation and function. We conclude that ExoU, by virtue of its PLA2 activity, augments and compensates for endogenous host neutrophil cPLA2α function, leading to enhanced transepithelial migration. This suggests that ExoU expression in P. aeruginosa can circumvent immune regulation at key signaling checkpoints in the neutrophil, resulting in exacerbated neutrophil recruitment.